African locus reduces the effect of ApoE ε4 allele in Alzheimer's disease. (December 2021) - Rajabli, Farid; Kunkle, Brian W.; Reitz, Christiane; Hendrie, Hugh C; Baiyewu, Olusegun; Ogunniyi, Adesola; Gao, Sujuan; Kushch, Nicholas A.; Hamilton‐Nelson, Kara L.; ,; ,; Beecham, Gary W.; et al.
Abstract: Background: Strong associations between ApoE ε4 and Alzheimer disease (AD) risk have been confirmed worldwide, but there is variability in the effect size across populations. African (AF)‐descent populations have a lower risk from ApoE ε4 compared to other populations. Studies in admixed populations showed that the AF ancestral background surrounding the ApoE gene reduces the ε4 risk allele effect. Our aim in this study is to identify genetic loci that show a protective effect in AF ancestral background. Method: Primary analyses included imputed data from 6, 417 African American (AA) individuals (Kunkle et al. 2020). We estimated global ancestry using a PC‐AiR approach that is robust to known and cryptic relatedness. To identify any protective factors interacting with ApoE in the AF local ancestry region, we performed association analyses using a logistic regression model with ApoE ε4 allele as an interaction term and adjusted for genome‐wide ancestry, age, and sex. We performed replication analysis using Whole Genome Sequence (WGS) data on 837 African LA ancestry individuals from Ibadan/Nigeria. Result: We identified a locus (rs10423769) that lies within a large cluster of pregnancy specific beta‐1 glycoproteins on chromosome 19, ∼ 2 mB from ApoE, with a significant interaction with the ApoE ε4 allele (β=‐0.53; SE=0.12;p‐value=1.2x10 ‐5 ; FDR adjusted p‐value<0.05) in the logistic regression model in the imputed AA samples. We replicated the association in the Nigerian population (β=‐1.35; SE=0.52;p‐value=9.6x10 ‐3 ). The epistatic interaction reduced the ApoE ε4 allele risk in AD individuals. Conclusion: This study identifies a new locus that reduces the risk effect of ApoE ε4 in AD in AF. rs10423769 is a common allele in AF‐descent populations (minor allele frequency (MAF) = 0.12), rare in Europeans (MAF = 0.003) and monomorphic in East Asians. Our results confirm that the AF ancestral background surrounding the ApoE gene harbors protective factors that help mitigate the effect of the detrimental ε4 allele.